Fracture failure analysis of baseplates in a fluidic amplifier made of WC-11Co cemented carbide (Fracture and Structural Integrity, 2013)
A fluidic amplifier is a crucial automatic control component in a liquid jet hammer used to drill hard formations in the oil industry. This study aims to determine the true causes of the fracture failure of baseplates in a fluidic amplifier made of WC-11Co cemented carbide in a very short period of time. Computational fluid dynamics (CFD), theoretical estimation, and finite element analysis (FEA) were employed to analyze the effect of static and dynamic loads on the strength of the baseplates. Fractographic, metallographic, and processing defect analyses were also carried out. The FEA results showed that the static and dynamic loads caused stress concentrations at the actual fracture locations, and the effect of working loads on material strength was allowable and safe. Fracture surfaces exhibited typical characteristics of a brittle fracture. The metallographic analysis revealed that a specific amount of brittle eta-phase (?-phase) was present in the material. The microstructure of the processing cutting zone was inspected and the results revealed that some voids, pores, and microcracks were formed on the processing surface. The manufacturing and processing defects resulted in low stress fracture failure of the baseplates.
Keywords: WC-Co cemented carbide